Child trafficking in Scotland - Beetham, Tanya (2020)
First paragraph: The Scottish Government Trafficking and Exploitation Strategy (2017) identified the need for Scotland-wide research to explore experiences of child trafficking in Scotland. This study, commissioned by the Scottish Government, aimed to provide an overview of how many children and young people had been identified as victims of human trafficking, to establish their geographic and demographic routes into Scotland and their experiences of professional responses. The research employed case file analysis and interviews with young people and professionals to illuminate these issues. For the index time-period for the research, no UK nationals were identified for the case file analysis. Consequently, the focus of the research was on children and young people who came to the UK across international borders